Solid solution island of the Co-Cr-Fe-Ni high entropy alloy system. (1st April 2017) - He, Feng; Wang, Zhijun; Wu, Qingfeng; Niu, Sizhe; Li, Junjie; Wang, Jincheng; Liu, C.T.
Abstract: Single-phase equiatomic CoCrFeNi high entropy alloy (HEA) is a promising high-entropy base with high tensile ductility and fracture toughness. However, the equal molar fraction of these elements is not a sufficient and necessary condition to obtain a single solid solution with high entropies. Instead, our combination of both calculated phase diagram (CALPHAD) calculations and experimental verifications indicate that the single phase region in the Co-Cr-Fe-Ni HEA system can be extended from a point to a large single phase solid solution island. The significance of this study is that HEAs can be designed with a high design diversity. Graphical abstract: The Co-Cr-Fe-Ni single-phase face cubic centered (fcc) high entropy alloy (HEA) is extended from a single equal-molar point to a large single phase solid solution island by using CALPHAD method together with systemic experimental verifications.